Key to sessile gnesiotrochan rotifers: Lacinularia and Sinantherina (Monogononta; Flosculariidae) - Davies, Natalie; Lafleur, Alexandre; Hochberg, Rick; Walsh, Elizabeth J.; Wallace, Robert L. (Zootaxa, 2025)
Understanding the general biology, biodiversity, ecology, and evolutionary history of organisms necessitates correct identification. Found worldwide in fresh, brackish, and some marine waters, rotifers can be difficult to identify due to their small size, complex characteristics, and dearth of keys to their identification. Moreover, many species lack a hard body wall (i.e., illoricate species), thus they are nearly impossible to identify when preserved. As a result detailed study of many illoricate rotifers is wanting. This is especially acute for the sessile rotifers where quality illustrations, either as line art or light or scanning electron photomicrographs, of adults and trophi is deficient. This leads to a serious impediment in providing a comprehensive accounting for some species. Lacinularia and Sinantherina (Monogononta; Gnesiotrocha; Flosculariidae) are two sessile genera in which the literature provides inadequate treatment. In this contribution we (1) provide simple, dichotomous keys for the identification of all valid species of both genera and (2) present collated information on their morphology thereby detailing where additional research is needed. Both keys focus on easily observable characters of adult female morphology, including features of their coronae, antennae, colony formation behaviors, and presence/absence of eyespots in the adults. We hope that our effort promotes additional research on these two genera, including better documentation of their trophi and general body morphology.